2014
DOI: 10.1152/japplphysiol.00906.2013
|View full text |Cite
|
Sign up to set email alerts
|

Absence of lateral gastrocnemius activity and differential motor unit behavior in soleus and medial gastrocnemius during standing balance

Abstract: In a standing position, the vertical projection of the center of mass passes in front of the ankle, which requires active plantar-flexor torque from the triceps surae to maintain balance. We recorded motor unit (MU) activity in the medial (MG) and lateral (LG) gastrocnemius muscle and the soleus (SOL) in standing balance and voluntary isometric contractions to understand the effect of functional requirements and descending drive from different neural sources on motoneuron behavior. Single MU activity was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 38 publications
4
60
0
3
Order By: Relevance
“…Given that the amplitude of anteriorposterior sway appears to be modulated by the accuracy of such impulses (52), high series compliance may serve to benefit control by minimizing fluctuations in torque in response to rate coding and motor unit recruitment. Although soleus has been evidenced to generate an ongoing background plantar flexor torque during standing (15,58), a compliant tendon may still act to limit inaccuracies in torque brought about by variability in motor unit firing rate (33).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the amplitude of anteriorposterior sway appears to be modulated by the accuracy of such impulses (52), high series compliance may serve to benefit control by minimizing fluctuations in torque in response to rate coding and motor unit recruitment. Although soleus has been evidenced to generate an ongoing background plantar flexor torque during standing (15,58), a compliant tendon may still act to limit inaccuracies in torque brought about by variability in motor unit firing rate (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we investigated the discharge behaviour of triceps surae MUs in standing balance with intramuscular single‐unit recordings (Héroux et al . ) and noted several instances where the same MU (time‐locked spike trains) was recorded from intramuscular electrodes located ∼5–6 cm from one another along the length of the muscle. Although anecdotal, this observation contradicted previous reports of small MU territories and regional activation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the flexor and extensor action exerted by the sural triceps is essential in maintaining the center of gravity during standing (Héroux et al, 2014). Besides the biomechanical action of MGM and PM, they help protect nerves and vessels coursing through the popliteal region; therefore, risk of neurovascular lesion increases with the agenesis of these muscles.…”
Section: Discussionmentioning
confidence: 99%